Factors Associated With The Incidence Of Postpartum Hemorrhage At Ansari Saleh Regional Hospital Of Banjarmasin In 2018 - Agustina, Rini (JURNAL KEBIDANAN BESTARI, 2021)
Abstract Postpartum hemorrhage is a direct cause of maternal death. Postpartum hemorrhage is bleeding over 500 ml after the baby is born. The incidence of postpartum hemorrhage at Ansari Saleh Regional Hospital of Banjarmasin in 2018 was 46 cases (0,02%) of 2268 postpartum mothers. The purpose of this study was to determine the factors related to the incidence of postpartum hemorrhage at Ansari Saleh Regional Hospital of Banjarmasin in 2018. The research design of this study uses an analytical survey method with a case control approach using a restrospective approach. Sampling technique using systematic random sampling. Case samples in this study were postpartum mothers who had postpartum hemorrhage at Ansari Saleh Ragional Hospital of Banjarmasin in 2018 as many as 46 respondents and the control sample in this study were 92 postpartum did not experience postpartum hemorrhage with a ratio of 1:2. Data analysis using using Chi-square test with significance level α = 0.05 and with a confidence level of 95%. The results of the study showed that mothers who had postpartum hemorrhage as many 46 respondents (33,3%), placental retention 13 respondents (9,4%), birth canal rips 7 respondents (5,1%), anemia in pregnancies of 57 respondents (41,3%), and twin pregnancies of 15 respondents (10,9%). The result of statistical tests showed that there is correlation between retention of the placenta (ρ=0,001), birth canal rips (ρ= 0,006), anemia in pregnancy (ρ= 0,000) and multiple pregnancies (ρ= 0,042) with the incidence of postpartum hemorrhage. In conclusion, there was a relationship between retention of the placenta birth canal rips, anemia in pregnancy and multiple pregnancies with the incidence of postpartum hemorrhage at Ansari Saleh Regional Hospital of Banjarmasin in 2018. Keyword: anemia in pregnancy, multiple pregnancy, postpartum hemorrhage, retention of the placenta